A fragment of a theoretical set and its strongly minimal central type - O.I. Ulbrikht; N.V. Popova (Қарағанды университетінің хабаршысы. Математика сериясы, 2023)
The paper defines a new class of algebras, the theory of which is a special case of Jonsson theories. This class applies to both varieties and Jonsson theories. The main results of this article are the following two results. In this article, an answer is obtained to the question of the equivalence of existential closure and algebraic closure of the model of the cosemantic class of a fixed spectrum of a Robinson hereditary variety. A criterion for strong minimality is obtained in the framework of the study of central types of central classes and fragments of a fixed spectrum.